Buffalo Fluffalo - Kalb, Bess, 1987-; Kraan, Erin (New York : Random House Studio, 2024)
A sweet and silly buffalo who tries to bluff and fluff his way into being bigger than he really is.
School Library Journal, December 2023
Booklist, November 2023
Bulletin (Center for Children's Books), December 2023
Kirkus Review, November 2023
K-3
N
Keywords: Bison -- Juvenile fiction; Animals -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Bison -- Fiction; Animals -- Fiction; Self-acceptance -- Fiction; Animal fiction; Stories in rhyme